2019
DOI: 10.3390/ijms20174146
|View full text |Cite
|
Sign up to set email alerts
|

Oral Bacteria and Intestinal Dysbiosis in Colorectal Cancer

Abstract: The human organism coexists with its microbiota in a symbiotic relationship. These polymicrobial communities are involved in many crucial functions, such as immunity, protection against pathogens, and metabolism of dietary compounds, thus maintaining homeostasis. The oral cavity and the colon, although distant anatomic regions, are both highly colonized by distinct microbiotas. However, studies indicate that oral bacteria are able to disseminate into the colon. This is mostly evident in conditions such as peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
164
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(180 citation statements)
references
References 185 publications
(238 reference statements)
9
164
1
6
Order By: Relevance
“…(F. nucleatum, F. mortiferum, and F. necrophorum) in CRC tissues, while bacteria belonging to Firmicutes and Bacteroidetes phyla were decreased [41]. This reduction in intestinal microbial diversity, as well as the overabundance of Fusobacterium, has been reported as common microbiota characteristics of CRC patients [37]. Interestingly, longer overall survival time was observed in CRC patients with low levels of F. nucleatum than in subjects with either moderate or high levels of this species.…”
Section: Oral and Intestinal Microbiota And Colorectal Cancermentioning
confidence: 71%
See 2 more Smart Citations
“…(F. nucleatum, F. mortiferum, and F. necrophorum) in CRC tissues, while bacteria belonging to Firmicutes and Bacteroidetes phyla were decreased [41]. This reduction in intestinal microbial diversity, as well as the overabundance of Fusobacterium, has been reported as common microbiota characteristics of CRC patients [37]. Interestingly, longer overall survival time was observed in CRC patients with low levels of F. nucleatum than in subjects with either moderate or high levels of this species.…”
Section: Oral and Intestinal Microbiota And Colorectal Cancermentioning
confidence: 71%
“…Interestingly, longer overall survival time was observed in CRC patients with low levels of F. nucleatum than in subjects with either moderate or high levels of this species. Going one step further, other studies have shown a connection between the detection of F. nucleatum and a poorer prognosis in CRC cases [42], suggesting the involvement of this bacteria as a non-invasive biomarker for CRC screening [37]. On the other hand, it is remarkable the high similarity found between F. nucleatum strains in tumor tissue and saliva from patients with CRC, which highlights an oral origin and strengthens the hypothesis about an orally driven intestinal dysbiosis in CRC [43,44].…”
Section: Oral and Intestinal Microbiota And Colorectal Cancermentioning
confidence: 96%
See 1 more Smart Citation
“…The oral cavity and colon are separate anatomical regions, but both are highly established by distinct microbiota. However, oral bacteria can spread to the colon (5) . This is mostly evident in the destruction of oral microbi-omes, such as periodontitis, where certain bacteria such as Fusobacterium nucleatum and Porphyromonas gingivalis have a pathogenic profile (6) .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, previous CRC studies showed enrichment of these three genera or their species in CRC patients (see e.g. Geng et al, 2014;Ugai et al, 2014;Kumar et al, 2017;Koliarakis et al, 2019), but had not detected these novel interactions. In conclusion, HARMONIES may reveal how multiple CRC-related taxa could potentially promote disease progression together.…”
Section: Analysis Of Microbiome Data From Colorectal Cancer Patientsmentioning
confidence: 91%